Productive Waqf and Poverty Alleviation: Government Contribution in Realizing Sustainable Development Goals - Pratama, Tommy; Sembada, Yoga Satria; Syahmirwan (Indonesian Scientific Publication, 2023)
Poverty is a serious challenge faced by many countries throughout the world, including Indonesia. This phenomenon is a big responsibility for the government so it is necessary to find comprehensive solutions to achieve sustainable development goals. One method of approach that is currently being intensively discussed is through the productive waqf pattern. Productive waqf applies the concept of productivity to waqf assets so that it is hoped that it will be able to make a significant contribution to poverty alleviation. This research identifies the strategies applied by the government in promoting productive waqf, namely through policy regulations, outreach to the community and efficient management. The results of this research show that the government's contribution to realizing sustainable development goals through productive waqf is very important. Productive waqf can optimize current waqf assets and increase public awareness of waqf with new innovations, namely cash waqf and share waqf. Effective supervision and transparency in the use of waqf funds are challenges that must be overcome.